Social Media as a Digital Communications Strategy; The Case of Hotel Enterprises in Cyprus - Papageorgiou, George; Marneros, Stelios; Efstathiades, Andreas (My University, 2020)
This paper investigates the use of social media platforms as digital communication tools for hotel enterprises and hospitality entrepreneurs. The aim is to examine whether hotel enterprises adequately capture the opportunity that social media provides in an era of digitization in order to effectively promote and advertise their products and services. Using a mix of qualitative and quantitative methods a survey is carried out to evaluate the activity and influence of social media in the hotel industry of Cyprus. Following a statistical analysis of the collected data, results revealed that social media tools are very powerful and valuable for the organizational performance and image of a hotel enterprise. However, findings also show that hotel managers are a long way from maximizing the utility of social media tools especially in developing plausible digital communications strategies. Definitely, hotel enterprises should invest more by hiring or training people to properly manage social media tools and respond to the demands of the new digital society.
Keywords: Digital Communications Strategy; Social Media; Digital Society; Hotel Enterprise